2023
DOI: 10.1002/adfm.202210192
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Metal Alloys as Zero‐Resistance Interfacial Modification Layers for Garnet‐Type Solid Electrolytes

Abstract: A solid-state battery with a lithium-metal anode and a garnet-type solid electrolyte has been widely regarded as one of the most promising solutions to boost the safety and energy density of current lithium-ion batteries. However, lithiophobic property of garnet-type solid electrolytes hinders the establishment of a good physical contact with lithium metal, bringing about a large lithium/garnet interfacial resistance that has remained as the greatest issue facing their practical application in solid-state batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The modified LLZGO achieved a high critical current density (CCD) of 12.05 mA cm −2 at room temperature and stable cycling for 2000 h at a current density of 2.0 mA cm −2 . Additionally, taking into account the advantages of alloying in promoting the transport of lithium ions at the interface, Cui et al 106 successfully prepared different metal alloy modifying layers on the surface of LLZTO using rapid quenching techniques (Figure 3D). Through extensive comparisons, they found that the AgSn 0.6 Bi 0.4 O x modifying layer exhibited negligible interface impedance, with a high limit current density of 20.0 mA cm −2 at 60 • C, providing a new research direction for the preparation of high-entropy alloy interfaces.…”
Section: Lithiophilic Layer Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified LLZGO achieved a high critical current density (CCD) of 12.05 mA cm −2 at room temperature and stable cycling for 2000 h at a current density of 2.0 mA cm −2 . Additionally, taking into account the advantages of alloying in promoting the transport of lithium ions at the interface, Cui et al 106 successfully prepared different metal alloy modifying layers on the surface of LLZTO using rapid quenching techniques (Figure 3D). Through extensive comparisons, they found that the AgSn 0.6 Bi 0.4 O x modifying layer exhibited negligible interface impedance, with a high limit current density of 20.0 mA cm −2 at 60 • C, providing a new research direction for the preparation of high-entropy alloy interfaces.…”
Section: Lithiophilic Layer Designmentioning
confidence: 99%
“…(D) Rapid sintering method for fabricating high‐entropy alloy interfaces. Reproduced with permission 106 . Copyright 2023, Wiley‐VCH.…”
Section: Interfacial Engineering For Anode Sidementioning
confidence: 99%
“…(c) Diagram of the melt-quenching procedure used to create the alloy-coated LLZTO electrolyte. This panel was reproduced with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Solutions To Address Interface Issuesmentioning
confidence: 99%
“…This technique has the potential to revolutionize Li metal engineering and be used in manufacturing Li metal batteries by the industrial system. In another investigation, Cui et al 165 established a metal quenching technique for evenly coating various interfacial modification layers based on metal alloys on the surface of garnet, illustrated in Figure 13c. They demonstrated that the interfacial resistance between lithium and garnet might be lowered at high current densities using a coating of ultrathin lithiophilic AgSn 0.6 Bi 0.4 O x .…”
Section: Magnetron Sputtering (Ms)mentioning
confidence: 99%
“…Garnet-type solid electrolytes have gained significant attention in recent years due to their stability. They exhibit good chemical compatibility with lithium metal and possess high ionic conductivity, which leads to enhanced safety and energy density in lithium ion batteries. , To address the issue of dendrite growth, lithium garnet (Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 , LLZTO) particles and lithium salt-free poly­(ethylene oxide) (PEO) were used to create a composite film by Zhang et al Remarkably, this solid electrolyte film demonstrated no dendrite growth even after 700 h of cycling. The nanoscale lithium ion conducting particles effectively improved electrical conductivity, while the insulating PEO in the PEO:LLZTO film electrolyte inhibited dendrite growth due to current limitations.…”
Section: All-solid-state Lithium Batterymentioning
confidence: 99%